2011
DOI: 10.4321/s1130-01082011000900001
|View full text |Cite
|
Sign up to set email alerts
|

Liver hydatidosis in the present decade

Abstract: Liver hydatidosis, a parasitic endemic disease affecting extensive areas in our planet, has been for decades a topic of debate in multiple medical and surgical forums because of its incidence, nonspecific symptoms, and diagnostic modalities, as well as the surgical procedures devised to solve this condition.On the other hand the relevant complications that may arise with disease progression and may involve multiple organs and neighboring structures causing disruption, migration, contamination, etc., turned thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…It also has the added benefit of being used without restrictions for aspiration, which is so important for the treatment of this disease. 13,14 It was not necessary to convert to open surgery in any of the cases, which coincides with the publications of other authors. 5,9,10 Mean hospital stay was 52 h. This also coincides with other authors, 9,12 although some reported a mean of 2 days.…”
Section: Discussionsupporting
confidence: 78%
“…It also has the added benefit of being used without restrictions for aspiration, which is so important for the treatment of this disease. 13,14 It was not necessary to convert to open surgery in any of the cases, which coincides with the publications of other authors. 5,9,10 Mean hospital stay was 52 h. This also coincides with other authors, 9,12 although some reported a mean of 2 days.…”
Section: Discussionsupporting
confidence: 78%
“…Abdominal echography shows the formation of biliary mud and a heterogeneous, hyperechoic mass of 45 mm adjacent to the gallbladder compatible with a diagnosis of hydatic cyst. Although the patient cohabits with dogs in an endemic area of hydatosis as is Spain (1,2), and the initial diagnosis leads to such condition, serology for hydatosis is negative. Abdominal CT scan (Fig.…”
Section: Case Reportmentioning
confidence: 99%